Ottumwa, Coffey County - Wheeler, Nickolas (Kansas State University, The Chapman Center for Rural Studies, 2012)
The lost town of Ottumwa, Coffey County, Kansas was settled by migrants of the Northern Midland Migration movement who shared similar progressive values and beliefs. The town experienced a brief period of prosperity, in which the town was home to a small college. This study uses early maps of the county, newspapers, personal reminiscences, and visits to the townsite to provide a history of Ottumwa, Kansas.
Nickolas Wheeler, “Ottumwa, Coffey County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/95.
Keywords: Ottumwa; Coffey County; Sauk and Fox Indians; Thomas Bowen; J.G. Shawbell; Neosho River